2011
DOI: 10.1155/2011/303510
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomal Myiasis: A Case Report and Review of the Literature

Abstract: “Myiasis” is considered in Hindu mythology as “God's punishment for sinners.” It is known to infest live human or animal tissue. Literature abounds with reports of myiasis affecting the nasal cavity, ear, nonhealing ulcers, exophytic malignant growth, and cutaneous tissue. But report of myiasis of the tracheal stoma is rare. Only a few cases of tracheal myiasis have been reported in literature. We report a case of tracheostomal myiasis in an elderly male. The species which had infested the stoma was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…This method proved to be effective where the larvae were successfully removed from most infested sites, even complex deep structures, including limb (13), mouth (11), eye (6), nose (4), perineal and inguinal regions (4), face (3), ear (2), scalp (2), and even the tracheostomy or pharyngostomy wounds (S1 and S3 Tables). The turpentine oil was commonly used as the effective suffocating agent [15, 33, 5055]. For instance, cotton buds or gauze impregnated with turpentine oil were usefully applied in the myiases treatment involving limbs, mouth, eye, ear, nose, facial tumor base [50, 51, 5355], and perineal and inguinal regions [15, 52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method proved to be effective where the larvae were successfully removed from most infested sites, even complex deep structures, including limb (13), mouth (11), eye (6), nose (4), perineal and inguinal regions (4), face (3), ear (2), scalp (2), and even the tracheostomy or pharyngostomy wounds (S1 and S3 Tables). The turpentine oil was commonly used as the effective suffocating agent [15, 33, 5055]. For instance, cotton buds or gauze impregnated with turpentine oil were usefully applied in the myiases treatment involving limbs, mouth, eye, ear, nose, facial tumor base [50, 51, 5355], and perineal and inguinal regions [15, 52].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, cotton buds or gauze impregnated with turpentine oil were usefully applied in the myiases treatment involving limbs, mouth, eye, ear, nose, facial tumor base [50, 51, 5355], and perineal and inguinal regions [15, 52]. But if the occlusive measure was applied to infested sites around tracheostomy and pharyngostomy tubes, this increases the risk of chemical pneumonitis [33].…”
Section: Resultsmentioning
confidence: 99%
“…The cotton buds or gauze impregnated with turpentine oil were usefully applied in the myiases treatment involving limbs, mouth, eye, ear, nose, facial tumor base [33,62-65], and perineal & inguinal regions [58,66]. If the oclusive measure was applied to the infested sites around the tracheostomy and pharyngostomy tubes, gave great caution for the high risk of chemical pneumonitis [67]. In one treat, the turpentine liniment was used in the scalp [68], In another, Bayer [69] reported that plugs soaked in 10% dextrose solution were successfully used to remove larvae from ear and nasal myiases due to C. bezziana , as the larvae seemed to have a liking for the dextrose solution, and consequently invade the plugs and stick to it, which faciliated larvae removal.…”
Section: Resultsmentioning
confidence: 99%
“…Although ether is described as successful in the few cases reports and references that are available, which include the American Society for Microbiology Myiasis Recommendations, they do not explicitly address how to compound the product or how to apply it to the affected area. 1,[11][12][13][14] Upon review of the literature, other cleansing methods are available as well. McIntosh and colleagues sought to assess the effectiveness of wound cleansing solutions on maggot mortality.…”
Section: Discussionmentioning
confidence: 99%